Double deboronation and homometalation of 1, 1′-bis(ortho-carborane)12. Issue 6 (23rd January 2017) - Thiripuranathar, Gobika; Chan, Antony P. Y.; Mandal, Dipendu; Man, Wing Y.; Argentari, Mario; Rosair, Georgina M.; Welch, Alan J.
Abstract : Diastereomeric diruthenium and dicobalt species derived from double deboronation and metalation of 1, 1′-bis( ortho -carborane) have been prepared and characterised. Abstract : Double deboronation of 1, 1′-bis( ortho -carborane) results in a mixture of racemic and meso diastereoisomers which are sources of the [7-(7′-7′, 8′- nido -C2 B9 H10 )-7, 8- nido -C2 B9 H10 ] 4− tetraanion. Consistent with this, metalation of the mixture with Ru( p -cymene) affords the diastereoisomers α-[1-(8′-2′-( p -cymene)-2′, 1′, 8′- closo -RuC2 B9 H10 )-3-( p -cymene)-3, 1, 2- closo -RuC2 B9 H10 ] (3 α) and β-[1-(8′-2′-( p -cymene)-2′, 1′, 8′- closo -RuC2 B9 H10 )-3-( p -cymene)-3, 1, 2- closo -RuC2 B9 H10 ] (3 β) in which the primed cage has undergone a spontaneous 3′, 1′, 2′ to 2′, 1′, 8′-RuC2 B9 isomerisation. Analogous cobaltacarboranes α-[1-(8′-2′-Cp-2′, 1′, 8′- closo -CoC2 B9 H10 )-3-Cp-3, 1, 2- closo -CoC2 B9 H10 ] (4 α) and β-[1-(8′-2′-Cp-2′, 1′, 8′- closo -CoC2 B9 H10 )-3-Cp-3, 1, 2- closo -CoC2 B9 H10 ] (4 β) are formed by metalation with CoCl2 /NaCp followed by oxidation, along with a small amount of the unique species [8-(8′-2′-Cp-2′, 1′, 8′- closo -CoC2 B9 H10 )-2-Cp-2, 1, 8- closo -CoC2 B9 H10 ] (5 ) if the source of the tetraanion is [HNMe3 ]2 [7-(7′-7′, 8′- nido -C2 B9 H11 )-7, 8- nido -C2 B9 H11 ]. Two-electron reduction and subsequent reoxidation of4 α and4 β afford species indistinguishable from5 . The reaction between [Tl]2 [1-(1′-3′, 1′, 2′- closo -TlC2 B9 H10 )-3, 1, 2- closo -TlC2 B9 H10 ] and [CoCpI2 (CO)] leads to the isolation of a further isomer of (CpCoC2 B9 H11 )2, rac -[1-(1′-3′-Cp-3′, 1′, 2′- closo -CoC2 B9 H10 )-3-Cp-3, 1, 2- closo -CoC2 B9 H10 ] (6 ), which displays intramolecular dihydrogen bonding. Thermolysis of6 yields4 α, allowing a link to be established between the α and β forms of3 and4 and racemic and meso forms of the [7-(7′-7′, 8′- nido -C2 B9 H10 )-7, 8- nido -C2 B9 H10 ] 4− tetraanion, whilst reduction–oxidation of6 again results in a product indistinguishable from5 .